Potential contamination of the coastal zone by eroding historic landfills. (September 2019) - Brand, James H.; Spencer, Kate L.
Abstract: Historically solid waste was commonly landfilled in the coastal zone in sites with limited engineering to isolate waste from adjacent coastal environments. Climate change is increasing the likelihood that these historic coastal landfills will erode releasing solid waste to the coastal zone. Historic coastal landfills are frequently located near designated ecological sites; yet, there is little understanding of the environmental risk posed by released waste. This research investigated inorganic and organic contaminant concentrations in a range of solid waste materials excavated from two historic coastal landfills, and the potential ecological impact should eroded waste be released to the coastal environment. Contaminant concentrations in the analysed waste materials exceeded sediment quality guidelines, indicating erosion of historic coastal landfills may pose a significant environmental threat. Paper and textile wastes were found to make a significant contribution to the total contaminant load, suggesting risk assessments should consider a wide range of solid waste materials. Highlights: Climate change may increase the risk of historic waste eroding into the coastal zone. Contaminant concentrations are highly variable between and within historic landfills. Release of solid waste would have significant ecological impact. Release of textiles, paper and wood may all present significant contamination risk. A screening risk assessment method needs to be developed to prioritise management.